Program IPTEK bagi Inovasi dan Kreatifitas Kampus IT Training & Service Center (ITSC) UNIKOM - Budi Herdiana; Bobi Kurniawan (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
The community of society is one of main activities required by a lecture as part of the tri dharma which aimed to apply and implement the scientific competence a lecturer to contribute positively especially for society needs. It activities do in UNIKOM is a form of the creativity between lecturers and students who want to develop their skill especially in information technology and entrepreneurship knowlegde, and therefore we established a business unit in 2014 was named "IT Training & Service Center (ITSC)". This business unit is formed by lecturers of electrical engineering, computer systems and informatics techniques. At the beginning of this business unit formed by the same vision and mission of them who joined the workshop activities hardware laboratory device repair activity related to computers, laptops, mobile phones and smartphones. The main target customers of this business unit is high school around Bandung and West Java, collage students, general society and office employees. Quality improvement of this business unit for 3 years we look the number of consumers who use our services increases every year. Where results of 2014 that the number of consumers when it was only 50 people include follow the training and service. For next year the number of customers increased to 235 people for training and 86 for service activities. While, for 2016 increased consumer more than twice with average increase every year more 100%.